2005
DOI: 10.1038/sj.onc.1208878
|View full text |Cite
|
Sign up to set email alerts
|

The retinoblastoma gene and its product are targeted by ICBP90: a key mechanism in the G1/S transition during the cell cycle

Abstract: The retinoblastoma protein (pRB) is encoded by the RB1 gene whose promoter contains several putative binding sites for ICBP90 (Inverted CCAAT box Binding Protein of 90 kDa), a transcriptional regulator of the topoisomerase IIalpha gene. ICBP90 has two consensus binding sites for pRB in its primary sequence. Here, we show that pRB and ICBP90 co-immunoprecipitate in cell extracts of proliferating human lung fibroblasts and of proliferating or confluent Jurkat cells. GST pull-down assays and immunocytochemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 48 publications
6
111
1
2
Order By: Relevance
“…Ccne expression peaks at 24 h in zebrafish regenerating livers and at 40 h in mice. Transcription of TOP2A is directly regulated by UHRF1 (23,28), and Top2a is up-regulated during mouse liver regeneration (38) with the same kinetics that we observe for Uhrf1. To determine whether heterozygous mutation of uhrf1 hinders its capacity to activate top2a during liver regeneration, we used Q-PCR to compare its expression in livers from uhrf1 ϩ/ϩ and uhrf1 ϩ/Ϫ zebrafish at the peak time of uhrf1 expression after PH (36 h).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Ccne expression peaks at 24 h in zebrafish regenerating livers and at 40 h in mice. Transcription of TOP2A is directly regulated by UHRF1 (23,28), and Top2a is up-regulated during mouse liver regeneration (38) with the same kinetics that we observe for Uhrf1. To determine whether heterozygous mutation of uhrf1 hinders its capacity to activate top2a during liver regeneration, we used Q-PCR to compare its expression in livers from uhrf1 ϩ/ϩ and uhrf1 ϩ/Ϫ zebrafish at the peak time of uhrf1 expression after PH (36 h).…”
Section: Resultssupporting
confidence: 57%
“…We show that the hi 272 line, which bears an insertion in the ubiquitin-like protein containing PHD and ring finger domains-1 (uhrf1) gene (21), is defective in physiologic liver growth in embryos and adults. UHRF1 (also called Np95 in mice and ICBP90 in humans) has been shown to require cell cycle progression in mammalian tissue culture cells (22)(23)(24)(25), and the expression of UHRF1 is up-regulated in cancer cells (24,(26)(27)(28). UHRF1 is a transcriptional activator of topoisomerase II␣ (top2a, refs.…”
mentioning
confidence: 99%
“…Indeed, a strong relationship was observed between the expression levels of the 2 genes, supporting the concept that UHRF1 regulation is under the control of the pRb/E2F1pathway. 46 It is of note that UHRF1 overexpression in the NSCLC tissue set was correlated with increased DNA methylation of both CDKN2A and RASSF1 promoters, and moreover that a much stronger association was observed when analyzing UHRF1 expression against a combined CDKN2A/RASSF1 methylation epigenotype. Thus, UHRF1 activity is important in maintaining the hypermethylation of certain TSGs.…”
Section: Discussionmentioning
confidence: 89%
“…We hypothesized that UHRF1 (Ubiquitin-like, containing PHD and RING Finger domains, 1) could be a major effector of the p73 deregulation, since this nuclear protein is known to be over-expressed in numerous cancer cell lines and tissues [8][9][10][11]. 4 Several studies have shown that UHRF1 participates in the control of cell proliferation and cell cycle transition from G1 to S, by regulating the expression of several genes, including RB1 and p16 INK4A [12,13]. This suggests that pathological overexpression of UHRF1, by repressing permanently the expression of specific tumor suppressor genes, could induce disorders in the G1/S progression and consequently promote tumor development [10].…”
Section: Introductionmentioning
confidence: 99%